Analysis of pharmaceutical crime as a bioterrorist threat in the framework of universal war in Indonesia - Adi Prasetya, Juliar (Institute of Computer Science (IOCS), 2024)
Currently, the development of the flow of exchange of goods in the global world is very fast, especially in the process of goods entering and exiting a country from another country, which requires a high level of supervision to be able to record and select existing goods. This causes problems related to the circulation of counterfeit drugs or have been modified or counterfeited using trademarks that are well-known in the community and have hazardous impacts on health. Bioterrorism is a real threat that must be anticipated and acted upon carefully. The method implemented in this research uses qualitative methodology using a phenomenological approach. Data collection techniques are carried out using literature studies and case studies that occur in the world community today. One of the bodies that supervises and takes action in the food and drug trade is the Food and Drug Supervisory Agency which has the authority to carry out the withdrawal of marketing permits for companies. On this occasion, researchers would like to take a deeper look at cases of counterfeiting and modification of medicines containing dangerous ingredients in their application from the perspective of asymmetric warfare using the threat of bioterrorism in the field of national defense and the actions that need to be taken to deal with the threat of bioterrorism, especially in Indonesia.